Trend following : how great traders make millions in up or down markets - Covel, Michael (Upper Saddle River, N.J. ; Harlow : Financial Times Prentice Hall, 2007)
Trend Following is the only long-term trading strategy proven to profit consistently in bull and bear markets alike. Now, Michael Covel demystifies this little-known strategy, using hard performance data to prove its extraordinary value. Covel introduces you to great traders who've built enormous fortunes with Trend Following--including Boston Red Sox owner John W. Henry, Bill Dunn and legendary Ed Seykota. You'll learn exactly why stock prices contain all the information you need to ride trends--and profit.
Includes bibliography (p. 405-412) and index.
Keywords: Investments; Επενδύσεις.; Speculation; Κερδοσκοπία.; Bear markets; Bull markets